Sex-based disparities in the association between uric acid levels and anxiety: a cross-sectional analysis of nationwide data in Korea - Soohyun Park; Joo O. Kim; Gyu Nam Park; Jae Won Oh; San Lee (BMC Psychiatry)
Abstract Background Uric acid has antioxidant properties, and several studies have suggested its neuroprotective effects. Despite reports of increased oxidative damage and decreased antioxidants in anxiety disorders, findings remain inconclusive. This study investigated the association between serum uric acid levels and anxiety symptoms, stratified by sex, using nationwide data from South Korea. Methods Data were derived from the Korea National Health and Nutrition Examination Survey, which included 2,228 males and 2,805 females. Presence of anxiety symptoms was defined as a Generalized Anxiety Disorder 7-item scale (GAD-7) score of ≥ 10. Study participants were categorized into three groups based on serum uric acid levels: 1 (lowest) to 3 (highest). Multivariable logistic regression analyzed the association between uric acid levels and anxiety symptoms, stratified by sex. Results Compared to reference group 2, females in group 1 had increased anxiety symptoms (odds ratio (OR) 2.28, 95% confidence interval (CI) 1.48–3.49). When anxiety symptoms were defined as a GAD-7 score of ≥ 5, females in groups 1 (OR 1.68, 95% CI 1.30–2.16) and 3 (OR 1.35, 95% CI 1.04–1.74) both showed more anxiety symptoms than group 2, with a U-shaped relationship between uric acid levels and anxiety symptoms. In males, uric acid levels weren't significantly linked to anxiety symptoms. Conclusions This study indicates that low serum uric acid levels are associated with a higher prevalence of anxiety symptoms only in females, suggesting involvement of oxidative stress in anxiety disorders and its sex-based variation.